Sustainable Financial Decisions and Firm Value: Empirical Evidence on the Role of Green Investment in Manufacturing Companies - Sitti Murniati; Herlina herlina (Institut Transparansi dan Akuntabilitas Publik (INSPIRING), 2026)
Purpose – This study aims to analyze the effect of sustainable financial decisions on firm value in manufacturing companies and to examine the mediating role of green investment in the relationship. The study is motivated by the growing importance of sustainable finance practices that integrate financial performance with environmental responsibility to support long-term corporate sustainability and the achievement of sustainable development goals. Design/methodology/approach – This research employs a quantitative approach using panel data analysis. The population consists of manufacturing companies listed on the Indonesia Stock Exchange during the observation period. The sample is determined using purposive sampling based on the availability of financial and sustainability reports. Data analysis includes descriptive statistics, classical assumption tests, and panel regression analysis. Furthermore, the mediating effect of green investment is tested using mediation analysis to evaluate whether green investment strengthens the relationship between sustainable financial decisions and firm value. Findings – The results indicate that sustainable financial decisions have a positive and significant effect on firm value. Additionally, sustainable financial decisions positively influence green investment, suggesting that companies integrating sustainability principles into financial strategies tend to allocate more resources to environmentally friendly investments. The findings also reveal that green investment positively affects firm value and acts as a mediating variable in the relationship between sustainable financial decisions and firm value. This implies that companies that actively invest in environmentally sustainable projects can enhance their market valuation and long-term competitiveness. Originality – This study contributes to the literature on sustainable finance and corporate value creation by integrating the concept of sustainable financial decision-making with green investment in explaining firm value within the manufacturing sector. The research highlights the strategic role of green investment as a mechanism that links financial sustainability practices to value creation, providing practical implications for corporate managers and policymakers in promoting environmentally responsible financial strategies.